Intravenous iron supplementation in distance runners with low or suboptimal ferritin - Garvican, L. A.; Saunders, P. U.; Cardoso, T.; MacDougall, I. C.; Lobigs, L. M.; Fazakerley, R.; Fallon, K. E.; Anderson, B.; Anson, J. M.; Tompson, K. G.; Gore, C. J. (Medicine & Science in Sports & Exercise, 2014)
Purpose: Iron deficiency is prevalent in distance runners and may impair endurance performance. The current practice of oral supplementation is slow and often not well tolerated. The aim of this study was to assess the efficacy of intravenous (IV) iron supplementation (ferric carboxymaltose) compared with oral supplementation (ferrous sulfate) on iron status, hemoglobin mass (Hbmass), and physiological indices of running performance in distance runners.